The Melanesian Spearhead Group in terms of Indonesia’s interest - ZAHIDI and MUSFIROH, M. Syaprin (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
This qualitative study aims to encompass Indonesia’s interest in seeking to join the MSG (Melanesian Spearhead Group). An in-depth interview was carried out with the Director of Directorate General of Asia, Pacific, and Africa under the Ministry of Foreign Affairs of the Republic of Indonesia aiming to obtain valid data supported by literature reviews. The findings indicate that Indonesia’s attempts to join the MSG or Melanesian intergovernmental organizations basically aim to maintain domestic stability which, in this context, refers to closing down separatist movements that still exist in Indonesia, such as the FPM (Free Papua Movement), that explicitly receive international support from Melanesian countries sharing the same racial background. In an effort to preserve the country’s sovereignty, Indonesia, in the era of President Joko Widodo, strives to join the MSG to prevent the Melanesian intergovernmental organization from supporting such separatist groups, which from Indonesia’s perspective could disrupt the unity of the Republic of Indonesia.

Artykuł przedstawia analizę jakościową korzyści, jakie upatruje Indonezja w członkostwie w międzyrządowej organizacji państw melanezyjskich (Melanesian Spearhead Group). Na podstawie pogłębionego wywiadu, przeprowadzonego z Dyrektorem Departamentu Azji, Państw Pacyfiku i Afryki w Ministerstwie Spraw Zagranicznych Republiki Indonezji, otrzymano aktualne dane, potwierdzone następnie literaturą przedmiotu. W rezultacie stwierdzono, że zasadniczym celem indonezyjskich starań o wstąpienie do MSG (międzyrządowej organizacji państw melanezyjskich) było utrzymanie wewnętrznej stabilizacji, co w tym kontekście odnosi się do wygaszenia działalności wciąż aktywnych w Indonezji ruchów separatystycznych, takich jak FPM (Ruch Wolnej Papui), otwarcie wspieranych przez państwa melanezyjskie, z którymi łączy je pochodzenie rasowe. Zabiegając o zachowanie suwerenności państwa, Indonezja pod rządami Prezydenta Joko Widodo, próbuje wstąpić do grupy MSG, aby zapobiec dalszemu wspieraniu grup separatystycznych przez tę międzyrządową organizację państw melanezyjskich, której działania mogą z punktu widzenia Indonezji zachwiać jednością Republiki Indonezji.
Międzyrządowa organizacja państw melanezyjskich (Melanesian Spearhead Group) a interes Indonezji
Keywords: Indonesia’s interest; Melanesian Spearhead Group; Separatist; interes Indonezji; międzyrządowa organizacja państw melanezyjskich (Melanesian Spearhead Group); separatystyczny